2020
DOI: 10.1364/boe.399949
|View full text |Cite
|
Sign up to set email alerts
|

Retinal layer thicknesses retrieved with different segmentation algorithms from optical coherence tomography scans acquired under different signal-to-noise ratio conditions

Abstract: Glaucomatous damage can be quantified by measuring the thickness of different retinal layers. However, poor image quality may hamper the accuracy of the layer thickness measurement. We determined the effect of poor image quality (low signal-to-noise ratio) on the different layer thicknesses and compared different segmentation algorithms regarding their robustness against this degrading effect. For this purpose, we performed OCT measurements in the macular area of healthy subjects and degraded the image quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…1 A), a region that has been shown to be advantageous over the commonly used 5-mm diameter ROI for mRNFL measurements. 37 It also reports peripapillary RNFL (pRNFL) thickness at a 3.45-mm diameter circle centered at the ONH ( Fig. 1 B).…”
Section: Methodsmentioning
confidence: 87%
“…1 A), a region that has been shown to be advantageous over the commonly used 5-mm diameter ROI for mRNFL measurements. 37 It also reports peripapillary RNFL (pRNFL) thickness at a 3.45-mm diameter circle centered at the ONH ( Fig. 1 B).…”
Section: Methodsmentioning
confidence: 87%
“…The device automatically segments and quantifies macular RNFL (mRNFL) thickness and ganglion cell-inner plexiform layer (GCIPL) within a 10-mm diameter circular region of interest (ROI) centered at the fovea ( Figure 1A), a region which has been shown to be advantageous over the commonly used 5-mm diameter ROI for mRNFL measurements. 37 It also reports peripapillary RNFL (pRNFL) thickness at a 3.45-mm diameter circle centered at the ONH ( Figure 1B). We further subdivided pRNFL into temporal, superior, nasal, and inferior.…”
Section: Data Collectionmentioning
confidence: 89%
“…First, we (back) transformed the logarithmically compressed intensity values; for this, we assumed that the 0–255 grayscale values in the 8‐bit image correspond to a 50 dB dynamic range in the (squared) spectrometer values, with the (squared) spectrometer output being linearly scaled. (Heikka, Cense, & Jansonius, 2020; Heikka, Ometto, et al, 2020) The B‐scan image is shown in Figure 1b; Figure 1c presents the corresponding A‐scans from the two locations marked in Figure 1b, based on both the greyscale values from the B‐scan image (blue) and the linearly scaled data (black). The RNFLT was calculated as the full width half maximum (FWHM) of the first peak in the linearly scaled A‐scan (marked with horizontal red line in Figure 1c).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work described the FWHM algorithm for segmenting the macular area. (Heikka, Cense, & Jansonius, 2020) Shortly, we developed the FWHM algorithm using MATLAB (Mathworks, version R2018a, Natick, Massachusetts: The MathWorks Inc.). First, we (back) transformed the logarithmically compressed intensity values; for this, we assumed that the 0-255 grayscale values in the 8-bit image correspond to a 50 dB dynamic range in the (squared) spectrometer values, with the (squared) spectrometer output being linearly scaled.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation